2014
DOI: 10.1111/jcmm.12239
|View full text |Cite
|
Sign up to set email alerts
|

Zinc is essential for the transcription function of Nrf2 in human renal tubule cells in vitro and mouse kidney in vivo under the diabetic condition

Abstract: Increasing evidence from human and laboratory studies showed the effect of zinc (Zn) on diabetic complications. Nuclear factor-erythroid 2-related factor 2 (Nrf2) plays important role in the prevention of oxidative damage. This study was to define whether Zn statues (deficiency or supplement) affect the Nrf2 expression and function, and also affect the damage severity of human renal tubular (HK11) cells exposed to high glucose (HG) with palmitate (Pal) and kidney of diabetic mice induced by multiple low-dose s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 54 publications
5
82
0
Order By: Relevance
“…Consistent with our work, several studies showed the ability of Zinc Chloride to control hyperglycemia [10] [43]. In addition, our results showed a significant increase in the mean arterial blood pressure in the diabetic control rats.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with our work, several studies showed the ability of Zinc Chloride to control hyperglycemia [10] [43]. In addition, our results showed a significant increase in the mean arterial blood pressure in the diabetic control rats.…”
Section: Discussionsupporting
confidence: 93%
“…Another study also showed the beneficial effects of Zinc Chloride in controlling hyperglycemia thus preserving liver architecture and ameliorating NO, MDA, superoxide dismutase (SOD) and GSH levels [10]. Our results, showing the antioxidant capacity of Zinc Chloride, are in accordance with Li et al, in 2014, who reported the role of Zinc Chloride in preventing renal oxidative damage via upregulation of nuclear factor-erythroid 2-related factor (Nrf2) [43].…”
Section: Discussionsupporting
confidence: 86%
“…Zinc has also been recognized as an intracellular second messenger (Murakami and Hirano, 2008;Prasad, 2014). For example, zinc is a signal for immune cell (Kabu et al, 2006;Yamasaki et al, 2012) and is essential for the transcription function of Nrf2 in diabetic models (Li et al, 2014). It may be that the high susceptibility to Cr(VI)-induced transformation that results from zinc deficiency in cell culture is associated with the loss of these zinc functions.…”
Section: Resultsmentioning
confidence: 99%
“…Zinc dyshomeostasis is intimately related to such disorders as metabolic syndrome, diabetes, and diabetic complications. Zinc has been reported to induce Nrf2 in an animal model and therefore considered an activator of Nrf2 [60].…”
Section: Zincmentioning
confidence: 99%